Theater as an alternative communication tool for living the otherness (REVISTA NODO, 2024)
This article addresses theater as an alternative communication tool to promote understanding and empathy between individuals in a world where communication is limited by interpretive filters and subjectivity. Theater, through acting, challenges the construction of closed identities and promotes openness towards otherness, allowing participants to live and represent life from the perspective of the other.The notion of the "other" as one who differs in beliefs, values, customs and experiences is highlighted, and it is pointed out that theater offers an opportunity to overcome the reification of the other by representing him/her/them in his/her/they diversity and complexity. The exercise of interpretation requires working on the inner configuration of the character, recognizing that both the character and themselves are being reconfigured in the process.Although it is recognized that theater has limitations, such as the impossibility of living from the interpretative framework of others and the risk that some actors or actresses focus on themselves instead of representing the other, its value as a tool that contributes to the construction of a more open and plural world is emphasized.